2008
DOI: 10.1016/j.nurt.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Gene Therapy for Movement Disorders

Abstract: Summary:After nearly 20 years of preclinical experimentation with various gene delivery approaches in animal models of Parkinson's disease (PD), clinical trials are finally underway. The risk/benefit ratio for these procedures is now generally considered acceptable under approved protocols. The current vehicle for gene delivery to the human brain is recombinant adeno-associated viral vector, which is nonpathogenic and non-self-amplifying. Candidate genes tested in PD patients encode 1) glutamic acid decarboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…Till now, gene therapy of PD using therapeutic genes encoding glial cell line-derived neurotrophic factor (GDNF) family has been extensively studied in animals, even advanced to clinical testing [14,15]. GDNF is generally believed to possess most potent trophic effects on dopaminergic neurons [16].…”
Section: Introductionmentioning
confidence: 99%
“…Till now, gene therapy of PD using therapeutic genes encoding glial cell line-derived neurotrophic factor (GDNF) family has been extensively studied in animals, even advanced to clinical testing [14,15]. GDNF is generally believed to possess most potent trophic effects on dopaminergic neurons [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, gene therapy of PD using therapeutic genes encoding GDNF family has been extensively studied in animals, even advanced to clinical testing (Hong et al, 2008;Mochizuki et al, 2008). Zhang and Pardridge (2009) reported that rats with experimental PD are treated with intravenous GDNF plasmid DNA (designated pTHproGDNF) and nonviral gene therapy using Trojan horse liposomes targeted with a MAb to the rat TfR.…”
Section: Gene Therapymentioning
confidence: 99%
“…(106, 108–113) One approach focuses on increasing dopamine production via direct delivery of genes involved in neurotransmitter synthesis while a second method is designed to change the neuronal phenotype bypassing the need for dopamine, both approaches should the ameliorate symptoms associated with PD. These therapies are also intended to delay development of end-stage disease, an important accomplishment in a progressive age-related disorder such as PD.…”
Section: Parkinson’s Disease Gene Therapy Clinical Trialsmentioning
confidence: 99%